Young children and the media: A discussion paper - Rutherford, L; Biron, D; Bittman, M (My University, 2010)
Drawing upon Australian and international research, this report examines the evidence on the positive and negative impacts of media on young children aged 0-8. It looks at the impact on wellbeing, education and socialisation; how young children engage in decision-making about media use and the creation of content. The focus of this project is to identify media strategies to enhance the wellbeing of young children, including how to facilitate the creation of content suitable for young children.
Keywords: Activities -- Children's Activities; Activities; Childhood and child development; Activities; Children's Activities; Childhood and child development